Ikterik Neonatorum Sebagai Efek dari Gigi Natal - Prima Nerito; Muhammad Hefdi; Evy Afiyah Syagran (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Hyperbilirubinemia in neonates or also called neonatal jaundice is a clinical condition in neonates characterized by yellow staining of the skin, mucosa, sclera. Icteric in infants is caused by many things including an increase in bilirubin due to the baby's liver has not been able to remove the bilirubin produced. Many cases occur is the lack of infant intake, so that the baby is difficult to urinate, so that the bilirubin produced cannot be removed and hyperbilirubin occurs. One of the causes of low intake in infants is the presence of natal teeth. Christmas teeth are teeth that grow at the beginning of birth. Although some cases do not cause serious complications, the complication that often occurs is irritation of the baby's tongue and mother's nipples during breastfeeding that needs attention is the swallowing of teeth that can cause interference with the baby. Case report. It was reported that a new mother gave birth normally to a 2-day-old baby and there was a hard lump in the anterior region of the mandibulla. On intraoral examination there are incisor teeth that grow in the mandibular region. This tooth causes the baby to be unable to breastfeed and makes the baby's body condition weak and eventually the baby becomes yellow. Case management. Removal of the Christmas teeth is carried out, then trains the baby to be able to breastfeed directly to the mother and regular observation and evaluation is carried out to monitor the development of the baby's general condition. Conclusion. It can be concluded that with good handling management will provide good results for mother and baby.